Diagnosis of Kaposi’s sarcoma - Alvian Arifin Saiboo; Dwi Murtiastutik; Etty Hary Kusumastuti; Putri Halla Shavira (Bali Dermatology Venereology and Aesthetic Journal, 2022)
Kaposi’s sarcoma has a picture reminiscent of several skin conditions, so further testing is needed to show the diagnosis of Kaposi’s sarcoma. Lymphatic endothelium cells infected with KSHV or human herpesvirus 8 form the basis of Kaposi’s sarcoma (KS), a multicentric tumor (HHV-8). These macules and plaques might be purple, reddish-blue or dark brown-black in color. KS is distinguished by this look.” Inflamed, ulcerated nodular lesions are common. They are neither unpleasant or uncomfortable, and the overlying skin or underlying tissues seldom die as a result of them. The gold standard examination in establishing the diagnosis of KS is histopathology. Several techniques that can be used for histopathological tissue retrieval are punch biopsy, shave biopsy, excision biopsy and incision biopsy. Immunohistochemical examination can also be performed to rule out the differential diagnosis. Immunohistochemical examination that we can do is with LANA-1, CD 34, CD 31, D2-40. Diagnosis of Kaposi’s sarcoma is difficult to diagnose only from a clinical picture, so similar diagnoses, i.e. histopathological and immunohistochemical examinations, are required.